The ICM Approach as a Way for Improving Leaning Science Subjects in High Schools in Tanzania (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
This paper focuses on the design and trial of the Integrated Chemistry Modules (ICM). The objective was to design the approach, thereafter try it out. Observations show that teachers and students appreciated the approach. A very significant improvement in performance in post-test in the first trial group (t (37) = 21, p < 0.001) was observed. Similarly A very significant improvement in performance in post-test in the second trial group (t (26) = 33, p < 0.001) was observed. It is concluded that video materials, classroom experiments and worksheets can assist students attain required competencies.Â